The Comparison of the convergence rate with different preconditioners for Linear Systems - Li, Aijuan (IJRDO- Journal of Educational Research, 2021)
In this paper, the preconditioned Gauss-Seidel iterative methods are proposed with different preconditioners. The comparison theorem is obtained under the different preconditioners when the coefficient matrix A of linear system is a nonsingular M- matrix. This generalizes the result in [1]. Numerical example are given to illustrate our theoretical result.